Histopathological effects of malathion and endosulfan on blood cells of wistar albino rats (Rattus norvegicus) - (:unkn) unknown (My University, 2008)
0

The aim of this study is an investigation of histopathological effects of malathion and endosulfan such as widely used insecticides in Turkey, on blood cells of wistar albino rats. In this study, we have used 20 wistar albino rats. These studies showed that erythrocyte cells have structural defects, degenerative cell size and surface shapes and also discomformity on membrane surfaces in rats administered endosulfan and malathion. It was also observed that these histopathological defects are related to dose increments. It has been demonstrated that the disconformity of leukocyte membranes is more pronounced when compared to erytrocyte membranes. It was also observed that the blood cells (leukocytes and erythrocytes) of rats in control group have a normal histological appearance. In conclusion, we have observed deformations in nucleus and cytoplasms of blood cells caused by different doses of malathion and endosulfan.
Keywords: Biyoloji